Um estudo de caso sobre o ensino de Libras nas escolas estaduais de Humaitá - Costa, Gabriela Almeida da (Brasil, 2024)
This Course Completion Work aimed to carry out a case study on the teaching of Libras in the State Schools of Humaitá in the state of Amazonas, in this way, it was verified how the teaching of Libras for deaf students occurs. For this, the methodologies used in the classroom by Libras teachers were observed, in addition to observing how the inclusion of these students occurs, and the challenges faced by teachers. The research brought to light the constant struggle against the lack of resources and the absence of looks at the deaf community within the school environment. The number of teachers who provide this service in the resource room and the number of students who participate in the services were identified. It was also sought to know what the training of the teachers is who serve deaf students. The study had a qualitative approach, described as a case study with the following input (Minayo, 2012; Yin, 2015), and was divided into three stages, namely: a bibliographic study, field research and the application of a questionnaire. We sought to know the strategies used to teach Libras, highlight the importance of the use of Libras and playful resources, as well as understand how the development of students happens. Therefore, the study highlights the urgency of expanding the debate about deaf students, as well as showing the adversities of the work of Libras teachers in the educational environment.